Fabrication of Aluminium Composite Using Stir Casting Process and Optimization of Machining Parameters - James, S.Johny; M. Kumar; B.Ramesh; K.Venkatesan; P. Kuppan (Asian Review of Mechanical Engineering, 2014)
In this study an attempt has been made to fabricate aluminium metal matrix composite with a composition of 5 wt% Silicon carbide and 4 wt% graphite using stir casting method. Silicon carbide has been added because it is well known for its hardness and its abrasive nature and graphite is a solid lubricant, result of its addition can change the surface roughness. The combined effect of four machining parameters including nose radius (R), cutting speed (s), feed rate (f), depth of cut (d) on the basis of single performance characteristic of surface roughness (Ra) were investigated. As Surface finish gives low co-efficient of friction and it shows the quality of the mechanical component. Optimal machining parameter has been calculated using design of analysis using Taguchi design or an orthogonal array.